Model Pembelajaran PAI Berbasis Problem Based Learning Dalam Pembentukan Karakter Tanggung Jawab Peserta Didik - Casdana Dana (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
A sense of responsibility is a character that is really needed in social life. This research aims to develop a Problem Based Learning model in Islamic Religious Education subjects in forming the responsible character. Classroom action research with data collection methods used are observation and tests. This research aims to determine the Islamic Religious Education learning process using the problem-based learning model in delivering PAI material, and the condition of students when participating in PAI learning using the problem-based learning model and to determine whether there is an increase in student learning outcomes and the character of student responsibility before and after take part in PAI learning using the problem-based learning model. in the pre-cycle, cycles I and II, there were significant differences in the learning outcomes before and after participating in PAI learning using the problem-based learning model. This can be seen through the test results above the specified KKM. Before the action was taken, only 33.00% of students got the KKM score, in the first cycle of action this increased to 53.00% of students who got the KKM score, then in the second cycle it became 81.00. Thus, it can be concluded that PAI learning using the problem-based learning model has proven to be effective in forming the responsible character.